2017
DOI: 10.1108/ijcma-05-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the relationship between cultural adaptation and argumentativeness

Abstract: Purpose This study aims to first explore the extent to which argumentativeness changed during the adaptation process among Muslim immigrants to France from 2006 to 2015 and, second, to examine the cultural fusion process. The study investigates the influence of intercultural contact on communication traits by exploring the extent to which members of the dominant cultural group adapt their argumentativeness over time. Design/methodology/approach Through a longitudinal panel study, the paper investigates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Argumentativeness research is increasingly conducted outside of the US and cross-culturally. In fact, as researchers have asserted argumentativeness as a trait is a culturally universal trait (Rancer and Avtgis, 2014), the 20-item argumentativeness measure or variations of it have been translated into many languages including Chinese, Korean, Japanese, Thai, French, German, Finnish, Spanish, Slovakian, Romanian, Russian, Turkish and other languages (Avtgis and Rancer, 2002; Croucher et al , 2013, 2016, 2018; Gronostay, 2019; Hsu, 2007; Park and Kim, 1992; Subanaliev et al , 2018; Suzuki and Rancer, 1994). Argumentativeness studies conducted outside of the US have shown that non-US based samples tend to differ in levels of argumentativeness from US-based samples.…”
Section: Argumentativeness Measurement Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Argumentativeness research is increasingly conducted outside of the US and cross-culturally. In fact, as researchers have asserted argumentativeness as a trait is a culturally universal trait (Rancer and Avtgis, 2014), the 20-item argumentativeness measure or variations of it have been translated into many languages including Chinese, Korean, Japanese, Thai, French, German, Finnish, Spanish, Slovakian, Romanian, Russian, Turkish and other languages (Avtgis and Rancer, 2002; Croucher et al , 2013, 2016, 2018; Gronostay, 2019; Hsu, 2007; Park and Kim, 1992; Subanaliev et al , 2018; Suzuki and Rancer, 1994). Argumentativeness studies conducted outside of the US have shown that non-US based samples tend to differ in levels of argumentativeness from US-based samples.…”
Section: Argumentativeness Measurement Issuesmentioning
confidence: 99%
“…In cross-cultural and non-US based studies of argumentativeness, it is common for many researchers to attribute differences in levels of argumentativeness to varying levels of individualism/collectivism, power distance, high/low context, self-construal and/or gender roles in societies (Rancer and Avtgis, 2014 for a review). While some researchers have ran validity studies of the argumentativeness measure or variations of it outside the US, these studies have not retained the 20-item scale (Croucher et al , 2016, 2018; Suzuki and Rancer, 1994) or have used only a 10-item or eight-item argumentativeness measure (Avtgis et al , 2008; Subanaliev et al , 2018). Other have relied on the work of Infante and Rancer (1982) to demonstrate validity in non-US samples or not reported validity analysis results (Croucher et al , 2009, 2010; Hsu, 2007; Klopf et al , 1991; Rapanta and Hample, 2015; Xie et al , 2015).…”
Section: Argumentativeness Measurement Issuesmentioning
confidence: 99%
See 1 more Smart Citation